Unia Europejska w programach głównych polskich ugrupowań politycznych po 2004 roku - Master, Beata (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: European Union in the political programs of the major political parties in Poland after 2004 Polish accession to the European Union was one of the strategic objectives of polish foreign policy after 1989. It succeeded in doing in 2004. The Polish membership in the European Union is supported a very large extent both by society and the majority of Polish political parties. However, the major political parties vary in their preferred vision of the integration processes in the European Union. This article aims to explain and compare these positions by examining the documents and political programs that were created after 2004, because they are an important part of European policy in Poland. Key words: programs of the political parties, integration processes, comparison of political programs